Physiological Responses and Match Characteristics of Men Doubles Badminton Athletes based on Playing Positions (Universitas Pendidikan Indonesia, 2024)
Men doubles badminton has been growing rapidly, requiring a study on match characteristics and physiological responses. To arrange an effective training program design and periodization, understanding the athlete physiological responses and match characteristics are necessary. This study examined the traits of male doubles badminton players according to their court positions (front and back). Laboratory tests and on-court simulations were administered in the study. Participants were athletes from an Indonesian elite badminton club aged 17-19 years. Measurements included anthropometrics, VO2max, blood lactic acid, heart rate, energy expenditure, and match statistics. Standardized equipment was used to measure the anthropometry, while treadmill test with gas analysis was used to measure VO2max. A portable analyser measured blood lactate during simulated matches, while Polar RC 3 GPS devices tracked heart rate and energy expenditure. Video analysis with Go Pro Hero 3+ cameras collected match statistics. The average VO2max was 56.4±5.7 ml/kg/min for both front and back players. Physical responses during gameplay showed significant differences (P0.005), with back players showing higher %HR max, calorie expenditure, and lactic acid levels than front players. Match statistics showed that back players had higher smashes (4.2±1.8) and unforced errors (6.3±7.3) (P0.005), while front players had higher drives (4.4±1.3) and net shots (4.2±1.2) (P0.005). Front and back players had different activity loads, as shown by maximum heart rate and stroke distributions, affecting lactic acid levels. Back players had higher maximum heart rates and more smashes than front players, indicating higher metabolic demands. These findings help tailor men doubles badminton position-specific trainings. The unique demands of each court position can be considered when designing more targeted and effective training programs using physiological adaptation and match data.